Tren Pengembangan Media Pembelajaran Virtual Tour: Implikasi bagi Pendidikan Dasar - Valya Audia Jihan Sahiroh; Muetya Insani; Rulyana Safitri; Khulatul Lutfiah (Yayasan Vifada Cendikia Indonesia, 2026)
The development of digital technology has driven in learning, especially through virtual tour-based learning media. This research analyzes trends in the development of virtual tour media in education, using the Systematic Literature Review (SLR) method from scientific publications between 2021-2025. Thru a search for articles on Google Scholar, 20 articles that fulfilled the inclusion criteria were successfully identified. The result show an increase in publications about virtual tour, peaking in 2023, with the most frequently used research method being Research an Development (R&D). The dominant media are web-based virtual tour and 360˚ videos. Research themes include media development, the use of virtual tour in learning, and their impact on learning outcomes, student interest, motivation, and engagement. The findings show that virtual tour create concrete, contextual, and interactive learning experiences and contribute positively to learning. However, studies on its application in primary education and focus on critical thinking skills, metacognitive skills, digital literacy, and 21st-century skills are still limited. Further research is necessary to enhance the effectiveness of virtual tours in facilitating innovative learning for 21st-century elementary education learners.